Developing a Design Approach from Scenario to Space in Interior Architecture Education via the Scamper Method: Christy Brown Example - H. Özlem Yurtgün (Iconarp International Journal of Architecture and Planning)
This study aims to investigate the role of empathy in the disciplines of cinema and interior architecture, with a particular emphasis on individuals with disabilities. The objective is to assess the potential benefits of this empathetic approach through the learning outcomes derived from a workshop study. Workshops are recognized as effective educational tools, as they facilitate a discussion and evaluation environment that transcends conventional standards of interior architecture education. The primary focus of this research is to cultivate empathy and human-centred thinking skills, specifically through the application of the Scamper method in interior architecture design. This study aspires to provide students with opportunities for abstract and creative thinking while fostering innovative design approaches that integrate various disciplines.